The microbiota metabolite indole inhibits Salmonella virulence: Involvement of the PhoPQ two-component system - Kohli, Nandita (PLoS One, 2018)
The microbial community present in the gastrointestinal tract is an important component of the host defense against pathogen infections. We previously demonstrated that indole, a microbial metabolite of tryptophan, reduces enterohemorrhagic Escherichia coli O157:H7 attachment to intestinal epithelial cells and biofilm formation, suggesting that indole may be an effector/attenuator of colonization for a number of enteric pathogens. Here, we report that indole attenuates Salmonella Typhimurium (Salmonella) virulence and invasion as well as increases resistance to colonization in host cells. Indole-exposed Salmonella colonized mice less effectively compared to solvent-treated controls, as evident by competitive index values less than 1 in multiple organs. Indole-exposed Salmonella demonstrated 160-fold less invasion of HeLa epithelial cells and 2-fold less invasion of J774A.1 macrophages compared to solvent-treated controls. However, indole did not affect Salmonella intracellular survival in J774A.1 macrophages suggesting that indole primarily affects Salmonella invasion. The decrease in invasion was corroborated by a decrease in expression of multiple Salmonella Pathogenicity Island-1 (SPI-1) genes. We also identified that the effect of indole was mediated by both PhoPQ-dependent and independent mechanisms. Indole also synergistically enhanced the inhibitory effect of a short chain fatty acid cocktail on SPI-1 gene expression. Lastly, indole-treated HeLa cells were 70% more resistant to Salmonella invasion suggesting that indole also increases resistance of epithelial cells to colonization. Our results demonstrate that indole is an important microbiota metabolite that has direct anti-infective effects on Salmonella and host cells, revealing novel mechanisms of pathogen colonization resistance.